The influence of collective action on the demand for voluntary climate change mitigation in hypothetical and real situations - Bodo Sturm; Reinhard Uehleke (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2015)
In this experiment, we investigate determinants of the individual demand for voluntary climate change mitigation. Subjects decide between a cash prize and an allowance from the EU Emissions Trading Scheme for one ton of CO2 that will be deleted afterwards. We vary the incentives of the decision situation in which we distinguish between real monetary incentives and a hypothetical decision situation with and without a cheap talk script. Furthermore, decisions were implemented either as purely individual or as a collective action using majority voting. We observe a significant hypothetical bias in the demand for voluntary climate change mitigation. In case of the individual decision situation this bias is caused solely by subjects with low income. Collective decision making affects demand positively in the hypothetical decision situation only.
Keywords: Q51; Q54; C93; 330; demand for voluntary climate change mitigation; public goods; collective action; hypothetical bias